Sign in
Please select an account to continue using cracku.in
↓ →
If $$a*b = (a + b) + (a - b)^{2}$$ and $$a \triangle b = (a + b)^{2} - (a - b)$$ then $$(3 \triangle 5):(3 * 5) =$$
$$11 : \sqrt{2}$$
$$11 : \sqrt{3}$$
11 : 2
11 : 3
Create a FREE account and get:
Terms of Service
CAT Formulas PDFCAT Syllabus PDFCAT Study Plan PDFCracku Brochure
Day-wise Structured & Planned Preparation Guide
By proceeding you agree to create your account
Free CAT Schedule PDF will be sent to your email address soon !!!